Internal Analysis of Factors Influencing the Use of Sleeping Beds (Utility Rate) - Trimo Trimo; Sandu Siyoto; Siti Farida (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Good service will increase the utilization of hospitalization (Utility rate) in Hospital, the factors that influence the utilization of service are procedure of service, service of doctor and nurse as well as facilities and infrastructure that exist in Hospital. The purpose of this study is to internal analysis of factors that affect the utilization of inpatient beds (Utility rate) in Caruban Hospital Madiun District. This research design using descriptive quantitative with Cross Sectional approach. The sample in this study amounted to 133 respondents. Random sampling sampling technique. The research instrument used questionnaire with Ordinal regression statistic test with α = 0,05. As many as 60.2% (80 respondents) stated that the service procedure is in good category. 50.4% (67 respondents) stated that the Doctor Service at Caruban Hospital of Madiun Regency is good. 81.2% (108 respondents) stated that Nurse Service is in good category. 45.9% (61 respondents) stated that the facilities and infrastructure in the category is quite good. 60.2% (80 respondents) stated that the utilization of the bed at Caruban Hospital of Madiun Regency is good. There is no influence of service procedure, there is influence of doctor service, nurse service and facility and infrastructure with utilization of inpatient bed (Utility rate) at RSUD Caruban Regency of Madiun. With good service from doctors and nurses as well as facilities that support the patient will provide information to families, relatives and others to take advantage of existing health services in hospitals Caruban Madiun District